Seminar on research results: the violation of the maxim of quantity produced by the undergraduate students at the english department STKIP YPUP Makassar - Fitriani, Fitriani (International Journal for Educational and Vocational Studies, 2021)
This study aims at analyzing the violation of the maxim of quantity produced by undergraduate students in research seminar and the reason why they violate this kind of maxim. The researchers applied qualitative research design by using observation and in-depth interview. Four undergraduate students were the participants of this research recruiting using purposive random sampling. The results show that most of the participants violated the maxim of quantity by doing circumlocution (not to the point), providing more explanation, and talking too much. They considered that it was valuable for them to provide more information than needed to obtain the attention of the examiners. They assume that the more they speak the good outcome for their research seminar will be accomplished because having more explanation means they master their research content well.